Experimenting with plumbatae and observations on their behavior - Emery, John (My University, 2010)
This study looked at the behavior of the plumbata, a unique Roman throwing weapon. This was done through the replication of weapon heads, shafts, and flights based off of previous research and through the incorporation of historical pictorial representations. The objective of this study was to include the important element of time and practices that had not previously been accounted for in earlier studies. This study also looked at near exact replication of the weapons based solely from the pictorial representations of historical manuscripts. This had been mentioned by previous researchers but had never been carried out. Basic results were that the weapon does indeed improve in range and consistency of behavior in flight providing increasing smooth flights and a max range of over 200 ft. The result of the picture based weapons was that they did not perform nearly to the ability of the non-pictorial based weapons.
Keywords: Archaeology -- Methodology.; Rome -- Military antiquities.; Weapons, Ancient -- Rome.